2012
DOI: 10.1111/j.1753-0407.2011.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression rate of newly diagnosed impaired fasting glycemia to type 2 diabetes mellitus: A study using the National Healthcare Group Diabetes Registry in Singapore

Abstract: The progression rate to T2DM is high in subjects with newly diagnosed IFG. Intensive lifestyle modification can be incorporated into their current yearly follow-up to prevent progression to T2DM, which is a growing problem in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is worth remembering that the rate of progression from prediabetes to DM is 6.8% per year 46. And among individuals categorized as prediabetic by both criteria (HbA 1c and fasting glucose), the cumulative risk of developing DM was 100% in a 5.6 years’ follow-up study 47.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth remembering that the rate of progression from prediabetes to DM is 6.8% per year 46. And among individuals categorized as prediabetic by both criteria (HbA 1c and fasting glucose), the cumulative risk of developing DM was 100% in a 5.6 years’ follow-up study 47.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-diabetes is a less common but important condition that constitutes an intermediate state between type 2 diabetes and healthy status. Several studies have identified that individuals with pre-diabetes have a high risk of developing diabetes, and the occurrence increases with age 2–4. Approximately 5%–10% of people with pre-diabetes become diabetic annually, although the progression rate varies by population and the definition of pre-diabetes 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…According to WHS 2009 data, Singapore is the country with the highest diabetes prevalence with 12 876 cases per 100 000 inhabitants, which is mainly observed in the Chinese community and is probably due to the intense urban lifestyle in Singapore 41. Although many laboratory studies have observed physiological effects of BT on glucose metabolism,17 18 42 43 the underlying mechanisms remain unclear. The results of human intervention studies are mixed44 and the role of caffeine has been suggested but not clearly established 43…”
Section: Discussionmentioning
confidence: 99%
“…The results of human intervention studies are mixed44 and the role of caffeine has been suggested but not clearly established 4345 Neyestani et al 42 found that regular daily intake of BT improves oxidative stress biomarkers and decreases serum C reactive protein levels in type 2 diabetic patients. Histological studies on pancreas cells published by Manikandan et al 17 concluded that the BT extract contributes to regeneration of damaged pancreas cells and protects pancreatic β-cells by its antioxidant action.…”
Section: Discussionmentioning
confidence: 99%